Meeting the challenges: carbon-hydrogen bond activation and cancer treatment - Wang, Hongwang (Kansas State University, 2011)
My thesis is divided into two parts. The first part is focused on studies of N-heterocyclic carbene (NHC) palladium(IV) intermediates, which are involved in oxidative addition mediated C-C, and C-O bond formation processes as well as in C-Cl bond forming reactions via a reductive elimination process. Bis-NHC-Pd(II) complexes have been reported as effective catalysts to mediate direct conversion of methane into methanol. However, a H-D exchange study revealed that the bis-NHC-Pd(II) complexes are not the active species responsible for the C-H bond activation reaction. This unexpected result implies that the high oxidation state bis- NHC-Pd(IV) species may be the real catalyst! The oxidative addition of methyl iodide to the bis- NHC-Pd(II)-Me2 complex led to the successful observation of the formation of a transient trimethyl bis-NHC-Pd(IV) intermediate by both 1H-NMR and 13C-NMR spectroscopy. Different oxidants such as O2, PhI(OAc)2, PhI(OTFA)2 and Cl2 reacted with the bis-NHC-Pd(II)-Me2 complex, and competitive C-C and C-O bond formations, as well as C-C and C-Cl bond formations were observed. Dioxygen triggered C-C bond formation under dry condition and both C-C and C-O bond formation in the presence of H2O gave strong indications that the bis-NHCPd( II)-Me2 complex can be oxidized to a bis-NHC-Pd(IV) intermediate by dioxygen. The reaction between the hypervalent iodine regents PhI(OAc)2 and PhI(OTFA)2 and the bis-NHCPd( II)-Me2 complex gave only reductive elimination products. Therefore, this system can act as a model system, which is able to providing valuable information of the product forming (functionalization) step of the C-H bond activation system. The reaction between chlorine and the bis-NHC-Pd(II)-Me2 complex resulted in a relatively stable bis-NHC-Pd(IV)-Cl4 complex, which was characterized by 1H-NMR spectroscopy and mass spectroscopy. The structure of bis- NHC-Pd(IV)-Cl4 was unambiguously established by X-ray crystallography. The second part of this thesis describes the synthesis of functionalized bimagnetic core/shell iron/iron oxide nanoparticles for the treatment of cancer. Biocompatible dopamineoligoethylene glycol functionalized bimagnetic core/shell Fe/Fe3O4 nanoparticles were prepared via ligand exchange, and purified by repeated dispersion/magneto-precipitation cycles. A porphyrin (TCPP) has been tethered to the stealth nanoparticles to enhance their uptake by tumor cells and (neural) stem cells. The stealth nanoparticles have been delivered in a mouse model to tumor sites intravenously by using the EPR (enhanced permeation and retention) effect. Magnetic hyperthermia proved to be very effective against B16-F10 mouse melanomas in Charles River black mice. After hyperthermia, the nanoparticles have shown a significant effect on the growth of tumor (up to 78% growth inhibition).
Keywords: Hyperthermia; Hydrocarbon activation; Bimagnetic nanoparticles; Palladium NHC-complexes; Stealth ligands; Chemistry, General (0485)